Thermal and mechanical characterisation of poly(ω -hydroxy pelargonate): a preliminary study for bioplastic - Siti Faieza Abd Hadi,; Muhammad Fadhli Kamaruzaman,; Jumat Salimon,; Mohd Firdaus Mohd Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Poly(ω-hydroxy pelargonate) or P(ω-OHP) is a potential biodegradable plastic which was prepared by melt condensation of its monomer (ω-hydroxy pelargonic acid). In this study, the performances of P(ω-OHP) in thermal and mechanical aspects, as well as the method employed for the monomer preparation was presented. Although this type of monomer is well established for pharmaceutical and cosmetic application, its possibility to be applied in bioplastic has not been extensively studied. Previous research also showed that the monomer preparation was rather complicated, expansive, and hazardous. Thus, this study offers the safe method through chemical modification which conducted in mild condition. The monomer structure was verified by using ESI-MS at 173.1 m/z with 92% purity. After melt-condensation process was carried out at 190 °C for 4 h, the formation of P(ω-OHP) was identified by the present of methylene ester bond indicated on 1H NMR peak at 4.05 ppm. The thermal properties were analyzed by DSC, TGA, and rheometer. P(ω-OHP) was melted at 72.8 °C and start to degrade at 220 °C with rheology analysis represented Newtonian flow at 80 and 180 °C. P(ω-OHP) contains 73.5% degree of crystallinity as determined by XRD with fewer amorphous area has affecting low mechanical value in hardness (31) and compressive strength (modulus 47.3 MPa, yield 1.03 MPa). The results suggest that P(ω-OHP) is thermally stable and physically hard and brittle. The findings have implications for bioplastic custom and subjected to improvement via polymer blending or block co-polymerization for application flexibility.